Formulation and Evaluation Of Poly Herbal Anti-Diabetic Capsule Dosage Form - Aggrey, Ernest; Ofori-Kwakye, Ph.D.,, Kwabena; Johnson, Ph.D.,, Raphael; El Boakye-Gyasi, Ph.D.,, Mariam; Asantewaa Osei, Ph.D., Yaa (Indonesian Journal of Pharmaceutics, 2023)
Traditional herbal liquid remedies may be converted into solid dosage forms for enhanced product stability, patient convenience and compliance. Hidden Treasure mixture (HTM) is an herbal decoction produced and used by Hidden Treasure Herbal Clinic(HTHC) in Ghana for the management of diabetes. The objective of the study was to transform the HTM herbal decoction into oral capsules. The amount of dried extract per dose (120 ml) of HTM decoction was determined together with the maximum wavelength of absorption. Different adsorbents were incorporated in the HTM extract at 75, 150, 225 and 300 mg per dose of HTM to facilitate adsorption of water and enhance the processing of the dried extracts. The adsorbent-HTM extract mix were dried in hot air oven at 60 ºC for 72 hours and subsequently processed into granules by dry granulation. The granules were evaluated for their ease of scrapping and processing, percentage loss in weight, flow properties and dissolution in aqueous medium. The weight of dried extract per dose was 350 mg. Light magnesium carbonate produced granules with the best ease of scrapping and processing and showed optimum release of 80.29% at 75 mg per dose. A maximum weight of 560 mg of HTM granules were used to fill size O capsule shells. Using LMC as adsorbent, the adsorbent-HTM granules were processed into capsules with talc and lactose as glidant and diluent respectively. The HTM capsules produced passed the stipulated British Pharmacopoeia quality control tests for hard capsules and can be used as replacement for the HTM decoction.Keywords: Decoction, Adsorbent extract-mix, Dry granulation, percent release,Granules.